PENGARUH PERHATIAN ORANG TUA, RESPON PADA IKLAN, INTENSITAS PERGAULAN TEMAN SEBAYA, DAN PEMAHAMAN SISWA PADA MATA PELAJARAN EKONOMI TERHADAP PERILAKU KONSUMSI SISWA KELAS VII SMPN 2 NGLEGOK KABUPATEN BLITAR TAHUN AJARAN 2015/2016 - Fitri Wulandari; Hari Wahyono; Agung Haryono (Jurnal Pendidikan Ekonomi, 2016)
Consumption behavior, also known as consumption patterns, is a way for someone to fulfill all her needs by buying and using goods and services required to meet the rational needs.thus, in order to fullfill the need, someone should choose what will be consumed so as not to buy anything that is not in use and buy something excessive or often called consumptive behavioral. Consumption behavior of students is influenced by several factors such as the parents 'attention, the response to the advertisement, the intensity of the peers, and students' understanding on economic subjects. Accordingly, it is necessary discussion about the influence of parental attention, the response to the advertisement, the intensity of peers, and students' understanding on economic subject on consumption behavior.